Interpolated reference model based fault tolerant sliding mode control for an octorotor. Issue 7 (3rd March 2022) - Vile, Liam; Alwi, Halim; Edwards, Christopher
Abstract: In this paper, a quasi‐linear parameter varying sliding mode control allocation law is proposed for the fault tolerant control of an octorotor. In the event of rotor faults/failures, an allocation law redistributes the control effort among the remaining healthy rotors. The sliding mode control law is designed to guarantee asymptotic tracking of a reference model which is tuned on‐line, through an interpolated feedback gain, to ensure that the control signals remain within their saturation limits. A method for designing the parameterised feedback gain is proposed which is shown to maximise a defined stability criteria whilst preventing undesirable performance characteristics in the reference model. The proposed scheme is tested on a non‐linear octorotor model in the presence of severe rotor failures and uncertainty/disturbances.